Influence of Frequency Converters on Insulation of Power Supply Cables at Oil-Producing Stations - D. I. Zalizny; O. G. Shirokov; S. N. Koukharenko; E. Y. Ustimenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
The paper considers consequences of negative frequency converter influence on insulation of  power supply cables used for submersible installations of electric-centrifugal pumps at oil-producing stations. The possible approaches to the solution of the problem are proposed on the basis of a harmonic analysis of actually measured voltages and currents in a cable.